Encouraging SMEs Towards Financial Literacy and Credit Facilities for a Sustainable Business - Antara, Made Ermawan Yoga; Martini, Ida Ayu Oka (Jurnal Pengabdian Pada Masyarakat, 2024)
Community service activities carried out in Paksebali Village, Klungkung Regency, Bali Province, were held with the aim of helping SMEs overcome obstacles, especially regarding financial literacy. This community service activity aims to increase the knowledge and insight of Paksebali village residents regarding financial literacy, guide them in preparing good financial reports, and utilize banking credit facilities to create sustainable SMEs. The problem that occurs in Paksebali Village is that many village residents who are involved in SMEs do not understand how to prepare good financial reports. They have also been unable to utilize credit facilities from banks wisely, as evidenced by the fact that there are still many bad loans or a lack of understanding about the mechanism for applying for bank credit. The first achievement of this activity was contributing in the form of knowledge transfer regarding financial literacy for Paksebali village residents, especially SMEs. Second, provide clear and clear guidance on how to prepare simple financial reports for SMEs and apply for credit as capital to build and develop their businesses. Third, the practice of preparing SME financial reports succeeded in increasing the insight of the Paksebali village SME actors, becoming more motivated by being directly involved in the practice of preparing financial reports.